2020
DOI: 10.1002/tcr.202000052
|View full text |Cite
|
Sign up to set email alerts
|

Novel Two‐Dimensional Porous Materials for Electrochemical Energy Storage: A Minireview

Abstract: Two dimensional (2D) porous materials have great potential in electrochemical energy conversion and storage. Over the past five years, our research group has focused on Simple, Mass, Homogeneous and Repeatable Synthesis of various 2D porous materials and their applications for electrochemical energy storage especially for supercapacitors (SCs). During the experimental process, through precisely controlling the experimental parameters, such as reaction species, molar ratio of different ions, concentration, pH v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…144 Another research study suggested that a core–shell structure with directed growth of ultrathin parallel birnessite on β-MnO 2 has great potential for application in high-performance ASCs. 43…”
Section: Application Of 2d Nanostructured Mn-based Materials In Super...mentioning
confidence: 99%
See 2 more Smart Citations
“…144 Another research study suggested that a core–shell structure with directed growth of ultrathin parallel birnessite on β-MnO 2 has great potential for application in high-performance ASCs. 43…”
Section: Application Of 2d Nanostructured Mn-based Materials In Super...mentioning
confidence: 99%
“…The optimized nanostructures not only supply open channels enabling the electrolyte to easily penetrate into the electrode, but also are used as supports to improve the structural stability. 42–44…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 241 ] Common porous materials include metal porous materials and nonmetal porous materials. [ 242,243 ] Metal porous material is also called metal foam. Foams have cellular structures with many voids (connected and randomly distributed within the material) and high porosity (e.g., porosity of higher than 0.9).…”
Section: Advanced Energy Storage Materialsmentioning
confidence: 99%
“…To solve the energy crisis, new energy storage technologies such as supercapacitors, 1–3 lithium-ion batteries, 4,5 sodium-ion batteries, 6–9 potassium-ion batteries 10 and other devices have been developed. In the past few years, graphene materials have attracted much attention in the research field of energy storage.…”
Section: Introductionmentioning
confidence: 99%